CONDITIONS OF DEVELOPMENT OF PROFESSIONAL MOTIVATION OF STUDENTS - Grinev, Dmitrii; Shlat, Natalia (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
Basing on the analysis of the structure of the motivational sphere of the personality, the identification of the essence of professional motivation in the student community, the article theoretically and experimentally substantiates the effectiveness of the complex of psychological and pedagogical conditions for the development of professional motivation of students in higher education: monitoring of personal and professional growth in the process of professional training; development and implementation of a system of methods and forms aimed at forming a professionally oriented process of cognition: psychological consultations on issues of professional orientation, personal self-determination, training on the development of professionally important qualities and motives of professional activity; modeling situations of upcoming professional activities; creation of the educational environment of the university for the application of acquired professional knowledge and skills. The article describes an empirical study of the structure of the motivational complex and the level of professional motivation of students. According to the results of the experiment, the need to create special educational conditions that underlie the development and implementation of the elective program aimed at increasing the level of professional motivation of students in higher education is revealed.